Incidencia de la reforestación en la subcuenca del río Casacay en el incremento periódico de su caudal - Ochoa Montero, Néstor (2015)
The topic: IMPACT OF REFORESTATION IN RIVER SUBWATERSHED CASACAY IN INCREASING ITS PERIODIC FLOW, researched it along the development of this work to achieve the aims and objectives and shall indicate in subsequent pages, which develops four chapters that will be theoretical and practical according to experiences gained in the development of expertise. It is noted that this issue is throbbing interest in our city, country and the world because if we recover the vegetation cover, reach a balanced ecosystem that is a threat of this century. I start analyzing the management of river basins, which is an issue that has been trying for several decades ago, it focuses on the harmonization between humans and the environment, becoming important for environmental management and improving the quality of life of man, but in fact it has not been a simple analysis of the existing problem. This work was done based on secondary data, and analyzing the results we have obtained in the field with each resident and authorities, these results will implement optimal alternatives to current industry conditions management. The Geographic Information Systems (GIS) as a tool for modeling and data expertise, helped to develop several management alternatives, such as ecological zoning - economic, ecological flow and floods, which were of great importance for decision-making. The results are presented as based plans and alternative management programs, which are directed to each of the elements of the basin, I propose solutions that involve local governments and institutions, which together with the help of the main authorities pose an improved quality of life and development of the population. For the socio-economic development need to run road infrastructure, potable water, dams for hydroelectric generation, transportation systems and other hydrocarbons. All these projects should be protected and provided for forestry measures of compensation corresponding to the inhabitants of these basins. At the end of this alternative and practical solutions to be applied throughout Ecuador but mainly in the management of this watershed with a focus on sustainable and sustainable development within which they are wont thesis establish forest plantations for the protection and recovery of damaged native forests, degraded forest lands, wildlife habitat deterioration, headers watershed, establishing connectivity corridors ecosystems; establish plantations for slope protection in road infrastructure, protection of micro watersheds contributors to the drinking water, protection of civil irrigation and hydropower generation, flood control and stabilization of sliding areas. Promote the active participation of communities and local agencies in afforestation and reforestation of protection, my research I have confirmed that the residents of the watershed were largely devoted to livestock and agriculture in general, as a result of these activities have been cut many trees and has increased livestock causing further contamination of the water source to be solved with a cantonal and provincial ordinance of land use around the different watersheds, with a green incentive for settlers of these sectors as an alternative to family support for reforestation and care of forests.